Application of Ant algorithm in virtual manufacturing cells - zhang, li; Wang, Xi (International Journal of Scientific Research and Management (IJSRM), 2018)
In this work, Ant algorithm is applied for scheduling tasks in virtual manufacturing cells (VMC). In virtual manufacturing cells, machines are randomly arranged in the workshop area. The task to be processed selects appropriate machines based on pre-determined objectives. The selection of the machinery turns into a complicated problem if there are several tasks for processing. There are a limited number of machines of any type in this workshop and the objectives are the minimization of the range of operation (sequence of tasks and starting time for each task) and the sum of the distances travelled by the entire piece. A number of standard problems were solved using the Ant algorithm in order to evaluate the efficiency of the algorithm. The results obtained show that the Ant algorithm offers good solutions in shorter times.